122k views
3 votes
Use the perfect square method
(3x + 3)^2 = 36

1 Answer

4 votes

Factor out the common term; 3

(3(x + 1))^2 = 36

Use the Multiplication Distributive Property; (xy)^a = x^ay^a

3^2(x + 1)^2 = 36

Simplify 3^2 to 9

9(x + 1)^2 = 36

Divide both sides by 9

(x + 1)^2 = 36/9

Simplify 36/9 to 4

(x + 1)^2 = 4

Take the square root of both sides

x + 1 = √4

Since 2 * 2 = 4, the square root of 2 is 2

x + 1 = 2

Break down the problem into these 2 equations

x + 1 = 2

x + 1 = -2

Solve the first equation; x + 1 = 2

x = 1

Solve the second equation; x + 1 = -2

x = -3

Collect all solutions;

x = 1, -3

User Tuby
by
4.6k points